Influência da luz LED em culturas de células-tronco mesenquimais in-vitro - Veloso, Marcelo Noronha [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Stem cells are defined as cells capable of self-renewal and differentiation into specialized cells when submited to external signalings in the enviroment. Among adult stem cells, mesenchymal cells occupy an important position because they can differentiate into mesodermal cells such as osteoblasts, adipocytes and chondrocytes. Cell therapy consists in the use of mesenchymal stem cells (MSC) in the treatment of degenerative diseases and harmed tissue reconstruction. Due to the longstanding and costly procedure for cultivation of MSC, it was proposed the use of low power light sources, such as light emitting diodes (LED), to optimize these factors. Recent works have shown a series of results from the influence of LED light on biological tissues such as increased rate of cell proliferation, increased RNA, DNA and ATP synthesis rate. The purpose of this study is to compare the biomodulator effect of LED light set at wavelengths 630nm ± 10nm and 805nm ± 10nm on the mesenchymal stem cells proliferation. For this, the mesenchymal stem cells culture adopted the procedure used in the Departament of Animal Reproduction and Veterinary Radiology of the Faculty of Veterinary Medicine and Animal Sciences of Botucatu. MSC were obtained from an adult horse bone marrow, and isolated by density gradient separation, with the FICOLL reagent and by centrifugation. The pellet containing the stem cells was removed and these were placed in low glucose DMEM culture medium, containing 10% fetal calf serum and antibiotics. The material was observed daily by inverted microscopy for monitoring the progression of the cells and subsequently the amount of cells were counted in a Neubauer counting chamber. The amount of MSC was obtained by cell culture seeded in 24 wells culture plate and segregated into three distinct groups: Group 1 was irradiated with wavelength set at 630nm ± 10 nm, Group... (Complete abstract click electronic access below)

Células-tronco são definidas como células capazes de auto-renovação e diferenciação em células especializadas quando submetidas a sinalizações externas do meio. Dentre as células-tronco adultas, as mesenquimais ocupam posição de destaque, pois podem se diferenciar em células mesodérmicas como osteoblastos, adipócitos e condrócitos. A terapia celular consiste no emprego de células tronco (CT) no tratamento de doenças degenerativas e reconstituição de tecidos lesados. Devido ao longo tempo e alto custo para o cultivo das CTM foi proposto o emprego de fontes de luz de baixa potência, como diodos emissores de luz (LED), a fim de otimizar tais fatores. Estudos recentes apresentam uma série de resultados da influência da luz LED em tecidos biológicos tais como: aumento da taxa de proliferação de células, aumento da taxa de síntese de RNA, DNA e ATP. O presente estudo tem como objetivo comparar os efeitos biomoduladores da luz LED nos comprimentos de onda 630nm ± 10nm (vermelho) e 850nm ± 10nm (infravermelho) sobre a proliferação de células-tronco mesenquimais. Os processos de coleta e cultivo celular seguiram critérios do Departamento de Reprodução Animal e Radiologia Veterinária da Faculdade de Medicina Veterinária e Zootecnia de Botucatu. As CTM foram obtidas a partir de medula óssea coletada de eqüinos adultos e isoladas através da separação por gradiente de densidade, com o reagente FICOLL, e por centrifugação. O pellet contendo células foi retirado e essas foram acondicionadas em meio de cultura DMEM de baixa glicose, contendo 10% de soro fetal bovino e antibiótico. O material foi observado diariamente por microscopia invertida para monitoramento da evolução celular e posteriormente contabilizada em câmara de Neubauer. A quantificação de CTM foi obtida através do cultivo das células semeadas em placas com 24 poços e segregada em três grupos... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Luz – Efeito fisiológico; Células-Tronco; Bioengenharia; Diodos emissores de luz